Periapical Status and Quality of Root Canal Fillings and Coronal Restorations in Iranian Population - Asgary, Saeed; Shadman, Bahareh; Ghalamkarpour, Zohreh; Shahravan, Arash; Ghoddusi, Jamileh; Bagherpour, Ali; Akbarzadeh Baghban, Alireza; Hashemipour, Maryam; Ghasemian Pour, Madjid (Iranian Endodontic Journal, 2010)
INTRODUCTION: This cross-sectional survey determined the dental prevalence of apical periodontitis (AP) in selected Iranian population, and evaluated the influence of the quality of root canal treatment (RCT) and their coronal restorations (CR) on the periapical status. MATERIALS AND METHODS: A total of 1064 panoramic radiographies were evaluated by two observers during 2009. The quality of RCT i.e. length/density of root fillings and CR in addition to periapical status of endodontically treated teeth were recorded. Their interrelationship was analyzed by Chi-squared, logistic regression and Spearman's rho statistics. Hosmer and Lemeshow tests were used for assessing fitness of logistic regression model and one sample k-s test was used for evaluating of normality of the data. RESULTS: Our results showed that 527 teeth (52%) of the endodontically treated teeth presented with AP radiographically. The percentages of teeth which fulfilled the criteria of an acceptable RCT or CR radiographically were 42.3 and 62.5 respectively. Incidence of AP among teeth with acceptable RCT (29.1%) was significantly lower than those suffering from unacceptable RCT (68.8%) (P<0.001). Moreover, adequate CR demonstrated a significantly better periapical status (58.6%) compared to teeth with inadequate CR (30.3%) (P<0.001). The incidence of AP ranged from 25.6% (good qualities) to 79.5% (bad qualities) (P<0.001). Cases with both unacceptable RCT/CR were 11 times more likely to have AP than cases with acceptable RCT/CR. The quality of RCT and CR were found to impact the periapical health of endodontically treated teeth.CONCLUSION: There are a significant high number of technically unacceptable endodontic and restorative treatments in Iran; therefore considerable efforts are needed to improve the standards of endodontic and restorative treatments.